ANALISIS STRATEGI PEMASARAN PRODUK AMPLANG UDANG DI PULAU KIJANG KECAMATAN RETEH - Friapliayanti, Anzu; ', Suarman; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Company Amplang shrimp is a company engaged in ready-to-eat foods, through the field observation shrimp firms do marketing using a strategy of concentration is a strategy that specializes some markets in sales because of lack of existing natural resources. So the company only sells products within the region and performs production only to the existing order. With the problems that exist then this research using SWOT Matrix to know the right marketing strategy for company to be able to run its business well, so get profit or profit. The result of the research concludes that the strategy used by the company and suggested for the company is 1. Growth oriented strategy if the company has SO strategy, that is strategy with internal strength strength and excellent opportunity 2. Stability Strategy if the company has WO strategy, that is strategy Which minimizes the weaknesses to seize the opportunities that exist, 3. Defense Strategy if the company has a WT strategy, a strategy that minimizes the weaknesses to overcome the threat.Key words : SWOT, Marketing Strategy, Strategy Analysis